The impact of psychological factors on sleep quality among public university students in Klang Valley, Malaysia - Anandavelu, Peshanteny; Ma’rof, Aini Azeqa; Abdullah, Haslinda (Human Resource Management Academic Research Society, 2022)
A good night's sleep is essential for human mental and physical health, and chronic sleep deprivation has been related to impaired neurobehavioral function. This study aims to determine the relationship between internet addiction, loneliness, and cognitive workload on sleep quality among public university students in Klang Valley. A total of 400 respondents involved from three public universities in Klang valley. A self-administered questionnaire was used as a tool for data collection. The result revealed that most of the respondents had moderate level of internet addiction, loneliness, and cognitive workload. Meanwhile, the result also showed that majority of the respondents scored low level severity of sleep quality. In addition, cognitive workload, loneliness and internet addiction were positively correlated with sleep quality issues. Multiple regression analysis showed that loneliness and cognitive workload were significant predictors of sleep quality issues among the students with cognitive workload as the strongest predictor. This study concluded that undergraduate students’ cognitive workload, loneliness and internet addiction were important in influencing the undergraduate students’ sleep quality issues. By understanding the impact of these psychological factors on sleep quality particularly among the undergraduate students, it helped to minimize the possibility of undergraduate students' sleep quality issues in order to promote and maintain a healthy lifestyle for them. Thus, the impact and implications of this study will be discussed.